E.B. O'Callaghan, Laws and Ordinances of New Netherland, 1638-1674, at 23 (1868) - (:unkn) unknown (My University, 1640)
Ordinance of the Director and Council of New Netherland, Providing for the Arming and Mustering of the Militia in Case of Danger: each provide himself with a good gun and keep the same in good repair and at all times ready and in order; and as they live at a distance from one another, every warned person is placed under his corporal in order that in time of danger he may appear at his post with his gun
Keywords: ARMED FORCES